Application of Fuzzy Algorithms and Analytical Hierarchy Process Modification in Decision Support Systems for Lazis Scholarship UNNES - Permadi, Dimas Bayu Satria; Alamsyah, Alamsyah (Scientific Journal of Informatics, 2020)
Lazis scholarship is a scholarship given to underprivileged students and does not yet have a system that supports the decisions to be taken. AHP is one of the most popular decision making methods in solving problems. But, AHP has several weaknesses. So that it will be modified based on previous research and the addition of fuzzy algorithms to get a better decision support system method. The results of this research were A009 students with the final result priority index value of 0.004176516 getting the first position. And the addition and modification in in this research is better than the standard decision support system. Fuzzy c-means produce scores that are more variable than manual grouping. Using sorting and ranking will produce a pairwise comparison matrix that is definitely consistent and has an average faster processing time is 0.028396 seconds, whereas with the standard method is 0.284415 seconds. Modification of alternative priorities also have a relatively faster average implementation time of 0.3165 seconds than the standard calculation with 2.6003 seconds. And modifications to the FPIV, if Â taking the top 25 ranking in the standard FPIV produces 3 the same value while in the modified FPIV there is 1 same value.